9(-24)-5((-24)-8)=

Simple and best practice solution for 9(-24)-5((-24)-8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(-24)-5((-24)-8)= equation:


Simplifying
9(-24) + -5((-24) + -8) = 0

Multiply 9 * -24
-216 + -5((-24) + -8) = 0
-216 + -5(-24 + -8) = 0

Combine like terms: -24 + -8 = -32
-216 + -5(-32) = 0

Multiply -5 * -32
-216 + 160 = 0

Combine like terms: -216 + 160 = -56
-56 = 0

Solving
-56 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7.5x+3.3-2x-6.7= | | Axb=A+13-b | | x+7.72=963 | | 4x+7=2x-15 | | -4-3z=23 | | (3i)-(6i)=0 | | 7=8y-17 | | 3(b+3)=42 | | (x^2)-x+400=0 | | 2(a-3)=40 | | 0.34=lnx | | 6x-1=125 | | 2+x+3x=34 | | y=x(x-2y)+2y(x+2y) | | -4x^2+11x-6=o | | (x^2)-x+20=0 | | 16q-18=qr+t | | 5x+6-x=-30 | | 0.5x+7=-9 | | G-24=14 | | x^3-12x^2+230.4=0 | | 25+4y=25+16 | | 5x-3(x-3)=4+5x-8 | | 0.5x+6=17 | | -4(6x-7)=-24x-28 | | -12x-65=-7x | | 5-(2x+2)=-(-3x+5)-x | | 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 |

Equations solver categories